The immunogenicity of anti-TNF therapy in immune-mediated inflammatory diseases: a systematic review of the literature with a meta-analysis - Garcês, Sandra; Demengeot, Jocelyne; Benito-Garcia, Elizabeth (Annals of the rheumatic diseases, 2013)
Background Immunogenicity of aTNFs is one of the mechanisms behind treatment failure. Objective To assess the effect of anti-drug antibodies (ADA) on drug response to infliximab, adalimumab and etanercept, and the effect of immunosuppression on ADA detection, in patients with Rheumatoid Arthritis, Spondyloarthritis, Psoriasis and Inflammatory Bowel Diseases. Data sources PubMed, EMBASE, Cochrane databases, article reference lists (through August 19 2012). Study selection Out of 2082 studies, 17 were used in the meta-analysis (1RCT; 16 observational studies). Data extraction Two reviewers extracted data. Risk ratios (RR), 95% CI, using random-effect models, sensitivity analysis, meta-regressions and Egger's test were calculated. Data synthesis Of 865 patients, ADA against infliximab or adalimumab reduced drug response rate by 68% (RR=0.68, 95% CI=0.12 to 0.36), an effect attenuated by concomitant methotrexate (MTX): <74% MTX+: RR=0.23, 95% CI=0.15 to 0.36; ≥74% MTX+: RR=0.32, 95% CI=0.22 to 0.48. Anti-etanercept antibodies were not detected. Of 936 patients, concomitant MTX or azathioprine/mercaptopurine reduced ADA frequency by 47% (RR=0.53, 95% CI=0.42 to 0.67), particularly when ADA were assessed by RIA (RR=0.36, 95% CI=0.23 to 0.55) compared with ELISA (RR=0.63, 95% CI=0.53 to 0.74). Conclusions ADA reduces drug response, an effect that can be attenuated by concomitant immunosuppression, which reduces ADA frequency. Drug immunogenicity should be considered for the management of patients receiving biological therapies.